0714 Where You Sleep Is More Important Than What You Do There: Relationships Between Sleep Environment And Insomnia Severity During Pregnancy. (27th April 2018) - Simpson, N; Rubens, S; Rangel, E; Manber, R
Abstract: Introduction: Cognitive behavioral therapy for insomnia places considerable emphasis on sleep interfering behaviors in bed (stimulus control and sleep hygiene recommendations), with lesser emphasis on the actual sleep environment and its potential to disrupt sleep. We developed and tested a Sleep Environment Questionnaire (SEQ) to better understand the association between these two factors and self-reported sleep difficulties. The SEQ includes 8 items representing an Ambient Sleep Disruptive Factors (ASDF) scale, such as bedpartner disrupting sleep or needing to attend to children at night, and 5 items representing Dysfunctional Sleep Behaviors (DSB), such as watching television or using the internet in bed. Methods: The SEQ was administered to 177 pregnant women with insomnia disorder (32.6 ± 5.05 years) as part of a large randomized controlled trial of non-pharmacological insomnia treatment during pregnancy. The Insomnia Severity Index (ISI), Edinburgh Postnatal Depression Scale (EPDS), and SEQ were administered at baseline. Results: The ASDF total score and six out of eight individual items were significantly correlated with ISI (p's <.05). Individual ASDF items correlated with ISI were sleep disrupted by: someone making noise other than snoring, movement from others sharing the bed, taking care of children in the middle of the night, pets, light, and uncomfortable temperature. The DSB total score was not related to ISI nor to any individual items. EDPS was significantly correlated only with the ADSF total score and one item of the ASDF (sleep disrupted by taking care of children; p's <.05). Regression analyses to test whether ASDF and DSB total scores predicted ISI found that the ASDF total score, but not the DSB total score, was a significant predictor of ISI after adjusting for depression scores (p=.001). Conclusion: Assessment and treatment of insomnia disorder needs to expand beyond standard treatment recommendations to better understand, and potentially mitigate, the negative effects of external sleep environment on sleep beyond what is addressed by the standard sleep hygiene recommendation to have a peaceful, comfortable and dark sleep environment. Support (If Any): NR013662.